Factors Associated with Self-Reported Voice Change in the Hospitalized Burn Population: A Burn Model System National Database Study - Kaitlyn L. Chacon; Edward Santos; Kara McMullen; Lauren J. Shepler; Carla Tierney-Hendricks; Audra T. Clark; Chiaka Akarichi; Haig A. Yenikomshian; Caitlin M. Orton; Colleen M. Ryan; Jeffrey C. Schneider (MDPI AG, 2024)
Voice plays a prominent role in verbal communication and social interactions. Acute burn care often includes intubation, mechanical ventilation, and tracheostomy, which could potentially impact voice quality. However, the issue of long-term dysphonia remains underexplored. This study investigates long-term self-reported voice changes in individuals with burn injuries, focusing on the impact of acute burn care interventions. Analyzing data from a multicenter longitudinal database (2015-2023), self-reported vocal changes were examined at discharge and 6, 12, 24, and 60 months after injury. Out of 582 participants, 65 reported voice changes at 12 months. Changes were prevalent at discharge (16.4%) and persisted over 60 months (11.6-12.7%). Factors associated with voice changes included flame burn, inhalation injury, tracheostomy, outpatient speech-language pathology, head/neck burn, larger burn size, mechanical ventilation, and more ventilator days (p < 0.001). For those on a ventilator more than 21 days, 48.7% experience voice changes at 12 months and 83.3% had received a tracheostomy. The regression analysis demonstrates that individuals that were placed on a ventilator and received a tracheostomy were more likely to report a voice change at 12 months. This study emphasizes the need to understand the long-term voice effects of intubation and tracheostomy in burn care.